Evaluation of ocean carbon cycle models with data-based metrics - Matsumoto, K.; Sarmiento, J. L.; Key, R. M.; Aumont, O.; Bullister, J. L.; Caldeira, K.; Campin, J. M.; Doney, S. C.; Drange, H.; Dutay, J. C.; Follows, M.; Gao, Y.; et al. (Geophysical Research Letters, 2004)
New radiocarbon and chlorofluorocarbon-11 data from the World Ocean Circulation Experiment are used to assess a suite of 19 ocean carbon cycle models. We use the distributions and inventories of these tracers as quantitative metrics of model skill and find that only about a quarter of the suite is consistent with the new data-based metrics. This should serve as a warning bell to the larger community that not all is well with current generation of ocean carbon cycle models. At the same time, this highlights the danger in simply using the available models to represent the state-of-the-art modeling without considering the credibility of each model.
811adTimes Cited:110 Cited References Count:17
Keywords: anthropogenic co2; pacific-ocean; radiocarbon

Estimates of anthropogenic carbon uptake from four three-dimensional global ocean models - Orr, J. C.; Maier-Reimer, E.; Mikolajewicz, U.; Monfray, P.; Sarmiento, J. L.; Toggweiler, J. R.; Taylor, N. K.; Palmer, J.; Gruber, N.; Sabine, C. L.; Le Quere, C.; Key, R. M.; et al. (Global Biogeochemical Cycles, 2001)
We have compared simulations of anthropogenic CO2 in the four three-dimensional ocean models that participated in the first phase of the Ocean Carbon-Cycle Model Intercomparison Project (OCMIP), as a means to identify their major differences. Simulated global uptake agrees to within +/- 19%, giving a range of 1.85 +/-0.35 Pg C yr(-1) for the 1980-1989 average, Regionally, the Southern Ocean dominates the present-day air-sea flux of anthropogenic CO2 in all models, with one third to one half of the global uptake occurring south of 30 degreesS. The highest simulated total uptake in the Southern Ocean was 70% larger than the lowest. Comparison with recent data-based estimates of anthropogenic CO2 suggest that most of the models substantially overestimate storage in the Southern Ocean; elsewhere they generally underestimate storage by less than 20%. Globally, the OCMIP models appear to bracket the real ocean's present uptake, based on comparison of regional data-based estimates of anthropogenic CO2 and bomb C-14. Column inventories of bomb C-14 have become more similar to those for anthropogenic CO2 with the time that has elapsed between the Geochemical Ocean Sections Study (1970s) and World Ocean Circulation Experiment (1990s) global sampling campaigns. Our ability to evaluate simulated anthropogenic CO2 would improve if systematic errors associated with the data-based estimates could be provided regionally.
417rwTimes Cited:187Cited References Count:64

Multiple anthropogenic tracer distributions in the ocean - Sabine, C. L.; Key, R. M.; Bullister, J. L.; Feely, R. A.; Lamb, M. F.; Millero, F. J.; Wanninkhof, R.; Peng, T. H.; Lee, K.; Kozyr, A.; Gruber, N. (Sixth International CO2 Conference, 2001)
id: 319